Analysis of The Relationship Between Volume, Speed, And Density On The MT Haryono Road Section Using The Greenshield, Greenberg, And Underwood Models - Sara Wibawaning Respati; Desak Made Ristia Kartika; Zharifah Alya Salsabil (International Journal of Science and Environment (IJSE), 2025)
Traffic congestion frequently occurs on MT Haryono Street in Balikpapan. Changes in travel patterns, population growth, and infrastructure development have a significant impact on the traffic conditions on this road. Effective congestion management requires a thorough understanding of traffic volume, speed, and density to develop appropriate strategies. This study aims to analyze the relationship between traffic volume, speed, and density using the Greenshield, Greenberg, and Underwood models, and to identify the model that best represents the traffic conditions. This quantitative research involved a field survey over a 400–meter segment of the road to determine the traffic volume, speed, and density. The collected data on volume, speed, and density were then analyzed using the Greenshield, Greenberg, and Underwood models. Based on the analysis of the relationship between traffic volume, speed, and density using the Greenshield, Greenberg, and Underwood models, the following primary conclusions are drawn. These models illustrate different relationships: Greenshield as linear, Greenberg as logarithmic, and Underwood as exponential. The analysis reveals a decline in speed with increasing volume and density, with Greenberg's model predicting higher speeds at low densities; however, this is less realistic. In contrast, the Greenshield and Underwood models more closely align with actual conditions. Among the models, Greenshield has the highest coefficient of determination (r² = 0.775), making it the most accurate in depicting this relationship.